Motivation on engineering students: A case study using theories and instruments for its measurement and development - Daniel López Fernández; Pedro P. Alarcón Cavero; Manuel Rodríguez Sánchez; Mª Luisa Casado Fuente (Universitat Politècnica de València, 2014)
Motivation is one of the key issues for the academic performance of university students, especially in engineering programs where their degree of difficulty leads to a low sense of self-efficacy and high rates of absenteeism and dropout in students. Since some time ago psychology has widely addressed the construct of motivation, and in recent decades psychopedagogic instruments, such as the MSLQ or the MAPE-3, have been designed in order to contribute to the motivation of university students. This paper presents a selection of theories, mainly framed on the understanding of the motivation processes and the identification of indicators that are useful to influence and evaluate the motivation of university engineering students. Based on these indicators, an instrument to diagnose students' motivation of Spanish Engineering Universities has been defined. This instrument has been used in an empirical and descriptiveexploratory study, with 92 students of the University Politécnica of Madrid. In this study theories and indicators to observe and stimulate motivation were identified. Besides, its adequacy to the target population has been evaluated, the developed instrument has been validated, issues of interest to the motivation of engineering students have been explored and particular features of motivation of these students of different Degrees and years have been identified.